Inheritance and quantitative trait loci analyses of the anthocyanins and catechins of Camellia sinensis cultivar 'Ziyan' with dark‐purple leaves. Issue 1 (13th May 2020) - Tan, Li‐Qiang; Yang, Chun‐Jing; Zhou, Bin; Wang, Liu‐Bin; Zou, Yao; Chen, Wei; Xia, Tao; Tang, Qian
Abstract : Owing to the potential health benefits, anthocyanin‐rich teas ( Camellia sinensis ) have attracted interest over the past decade. Previously, we developed the cultivar 'Ziyan, ' which has dark‐purple leaves because of the accumulation of a high amount of anthocyanins. In this study, we performed a genetic analysis of this anthocyanin‐rich tea cultivar and 176 of its naturally pollinated offspring. For two consecutive years, we quantified the anthocyanins and catechins of 'Ziyan' and the offspring population. While >60% of the offspring accumulated less than half of the amount of anthocyanins of 'Ziyan, ' 17 (2018) and 15 (2019) individuals exceeded 'Ziyan' in anthocyanin content. A negative correlation between anthocyanin and total catechin content (r = −0.59, P < 0.001) was observed. The population was genotyped with 131 SSR markers spanning all linkage groups of the C. sinensis genome. Kruskal‐Wallis tests identified 10 markers significantly associated with anthocyanins, catechins and their ratios in both years. Quantitative trait locus (QTL) analyses using the interval mapping method detected 13 QTLs, suggesting the dark‐purple trait of 'Ziyan' is because of the pyramiding of anthocyanin‐promoting alleles on at least five linkage groups. Two genetic loci reversely related to anthocyanin and total catechin contents were identified. This study provides valuable information for genetic improvement of purple tea cultivars and for fine‐mapping related genes.